Simone Weil's Method: Essaying Reality through Inquiry and Action. Issue 3 (2nd September 2021) - Davis, Benjamin P.
ABSTRACT: I read a selection of Simone Weil's political philosophy in the way that she reads Marx – as forming "not a doctrine but a method of understanding and action." My claim is that Weil's method is likewise twofold: she attempts to understand the world through inquiry, then she tests her understanding through action. First, I read "Reflections Concerning the Causes of Liberty and Social Oppression" (1934). In that essay, inquiry, exemplified by Weil's calling into question the term "revolution, " is her way of understanding reality around her, including forces of oppression and possibilities for liberation. Second, I read her "Factory Journal" (1934–1935), which records how she tested her theories from "Reflections" by placing herself in French factories. My conclusion states the fruits of Weil's method for philosophy today: an interrogation of present political keywords (resistance, resilience) and a practice of philosophy as a way of life.